2012
DOI: 10.1111/j.1365-313x.2012.04928.x
|View full text |Cite
|
Sign up to set email alerts
|

Putative members of the Arabidopsis Nup107‐160 nuclear pore sub‐complex contribute to pathogen defense

Abstract: SUMMARYIn eukaryotic cells, transduction of external stimuli into the nucleus to induce transcription and export of mRNAs for translation in the cytoplasm is mediated by nuclear pore complexes (NPCs) composed of nucleoporin proteins (Nups). We previously reported that Arabidopsis MOS3, encoding the homolog of vertebrate Nup96, is required for plant immunity and constitutive resistance mediated by the de-regulated Toll interleukin 1 receptor/nucleotide-binding/leucine-rich repeat (TNL)-type R gene snc1. In vert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
98
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(99 citation statements)
references
References 58 publications
(95 reference statements)
1
98
0
Order By: Relevance
“…In a proteomic screen, HOS1 interacts with the nuclear pore proteins RNA EXPORT FACTOR1-green fluorescent protein (GFP) and the nucleoporin Nup43-GFP (Tamura et al, 2010) and associates with the nuclear periphery (Lazaro et al, 2012). Nuclear pore complexes are required for the export of mRNA from the nucleus; mutating components of the nuclear pore complex results in abnormal mRNA export as shown by in situ hybridization against poly(A)-containing mRNA (Dong et al, 2006b;Parry et al, 2006;Wiermer et al, 2012). Therefore, we used in situ hybridization to detect poly(A)-containing mRNA to determine if HOS1 plays a role in nucleo-cytoplasmic mRNA export.…”
Section: Hos1 Is Necessary To Maintain Wild-type Circadian Clock Perimentioning
confidence: 99%
See 1 more Smart Citation
“…In a proteomic screen, HOS1 interacts with the nuclear pore proteins RNA EXPORT FACTOR1-green fluorescent protein (GFP) and the nucleoporin Nup43-GFP (Tamura et al, 2010) and associates with the nuclear periphery (Lazaro et al, 2012). Nuclear pore complexes are required for the export of mRNA from the nucleus; mutating components of the nuclear pore complex results in abnormal mRNA export as shown by in situ hybridization against poly(A)-containing mRNA (Dong et al, 2006b;Parry et al, 2006;Wiermer et al, 2012). Therefore, we used in situ hybridization to detect poly(A)-containing mRNA to determine if HOS1 plays a role in nucleo-cytoplasmic mRNA export.…”
Section: Hos1 Is Necessary To Maintain Wild-type Circadian Clock Perimentioning
confidence: 99%
“…Circadian clock mutants used have been described and are lhy-20 (Michael et al, 2003), che-2 (Pruneda-Paz et al, 2009), prr9-10 (Ito et al, 2003), prr7-11 (Yamamoto et al, 2003), prr5-11 (Yamamoto et al, 2003), prr3-1 (Para et al, 2007), toc1-101 (Kaczorowski, 2004), gi-201 (MartinTryon et al, 2007, lux-5 (Hazen et al, 2005), elf3-1 (Hicks et al, 1996), and ztl-105 (SALK-069091) (Martin-Tryon et al, 2007). Previously published mRNA export mutants were obtained from the Nottingham Arabidopsis Stock Centre and have been previously described: sar1-4 (SALK_126801) (Parry et al, 2006), los4-1 (Gong et al, 2005), nua-3 (SAIL_505_H11) (Xu et al, 2007), nup107-1 (SALK_057072) (Wiermer et al, 2012, Clarkson et al, 1997, and hst-7 (Bollman et al, 2003).…”
Section: Plant Materialsmentioning
confidence: 99%
“…Ten nucleoporins have been isolated and functionally characterized in plants: NUP160/ SAR1, NUP133, NUP96/SAR3/MOS3, NUP88/MOS7, NUP75/NUP85, NUP1/NUP136, RAE1, TPR/NUA, NUP107, and NUP62 (Zhang and Li, 2005;Dong et al, 2006;Kanamori et al, 2006;Parry et al, 2006;Jacob et al, 2007;Saito et al, 2007;Xu et al, 2007;Lee et al, 2009;Tamura et al, 2010;Tamura and Hara-Nishimura, 2011;Wiermer et al, 2010Wiermer et al, , 2012Zhao and Meier, 2011). These nucleoporins have been shown to regulate cell division, hormone signaling, response to stress, rhizobial and fungal symbiosis, flowering, and other aspects of plant development.…”
mentioning
confidence: 99%
“…In plants, it is composed of eight nucleoporins: Nup160, Nup133, Nup107, Nup96, Nup85, Nup43, SEC13, and SEH1 (Fig. 2) (Xu and Meier, 2008;Tamura et al, 2010;Wiermer et al, 2012). Electron microscopic and biochemical analyses revealed that the yeast Nup84 subcomplex has a 40 nm long, Y-shaped, triskelion-like structure (Siniossoglou et al, 2000;Kampmann and Blobel, 2009).…”
Section: Outer Ring Inner Ring and Linker Nucleoporins (Scaffold Numentioning
confidence: 99%